Tingkat Kebutuhan dan Perubahan Hasil Perawatan Ortodonti Berdasarkan Indeks ICON (Kajian pada Pasien Klinik Ortodonti RSGM-P FKG USAKTI) - Tika Savira Ibrahim; Riko Nofrizal (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Malocclusion is a common oral health problem. Orthodontic treatment is needed to treat malocclusion so that the teeth can achieve a good occlusion. The need for orthodontic treatment and the outcome can be measured using an orthodontic index. One of the orthodontic indexes that can measure the need for orthodontic treatment and the outcome is ICON index. Purpose: To find out the level of need and changes in the outcome of orthodontic treatment in the RSGM-P FKG USAKTI’s orthodontic clinic based on the ICON index. Method: This research is a descriptive observational study with a cross-sectional design. Examination and measurement of the study model of patients aged 8 – 12 years old who came to the orthodontic clinic of RSGM-P FKG USAKTI in January 2018 – December 2019 was carried out based on the ICON component. a score was given based on the condition of the teeth in the study model. Result: the assessment of 48 patients showed that 36 patients (75%) were categorized as needing orthodontic treatment and 12 patients (25%) were categorized as not needing orthodontic treatment. Treatment result were assessed with improvement level. It was found that no subject was categorized as greatly improved, 5 patients (10,42%) were categorized as substantially improved, 15 patients (31,25%) were categorized as moderately improved, 15 patients (31,25%) were categorized as minimally improved, and 13 patients (27,08%) were categorized as not improved/worst. Conclusion: The research results illustrate that most of the patients treated at the orthodontic clinic RSGM-P FKG USAKTI require orthodontic treatment and the improvement level are mostly categorized as moderately improved and minimally improved.